From the Archives of Levon Mkrtchyan (“Fedor Aleksandrowich has spoke-wrote truthfully…” / Notes on Fedor Abramov) - SAHAKYANC, KARINE (Bulletin of Yerevan University H: Russian Philology, 2021)
The paper follows a number of other papers, earlier published in this magazine under the single title “From the Archives of Levon Mkrtchyan” (2015 №№ 1-3; 2018, № 1). The author presents materials, in which Armenian connections and impressions of Fedor Abramov (1920-1983) – one of the best Russian prose-writers in decades 1950-1970 are reflected. Diary notes of L.Mkrtchyan, made on the public meeting with the writer in the Yerevan State University, their correspondence, other documents are published. Special attention is attached to friendly and creative contacts of F.Abramov and S.Kaputikyan.